Niektóre Zagadnienia Podobieństwa Modelowego Elementów Zbrojonych - Szulc, J.E. (Engineering Transactions, 1961)
This paper discusses the laws of similitude existing between reinforced models and their prototypes i.e. reinforced elements. The tests on models (for instance photoelastic ones) of reinforced elements (for instance reinforced or prestressed concrete) may be carried out in two ways: 1. The model is made of a homogeneous material, the influence of the reinforcement on the stress distribution being neglected. 2. The model is made, similarly to the prototype, of two materials, different, in general, from those of the prototype. The second method is certainly more correct but when it is applied some additional laws of similitude must be fulfilled. It can be shown [1], that the fulfilment of condition (2.4), as required by some authors (for instance [2]), is not necessary, It is sufficient to satisfy condition (2.5), which is more general. Another condition of similitude is equality of Poisson’s ratios for both the model and prototype (2.3). This condition being impossible to satisfy, in general, in tests on models, a certain error appears in the results obtained (for instance in the stress distribution). This error may be evaluated only for particular cases. Its analysis for two types of reinforced concrete elements (Fig. 1a and 1b) shows that the effect of different Poisson’s ratios is not significant (Fig. 3, 4, 5). Thus, the application of reinforced models for such structures is justified.